2015
DOI: 10.1063/1.4922110
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical calculations of state-to-state cross sections and rate constants for the F + DCl → Cl + DF reaction

Abstract: We present accurate state-to-state quantum wave packet calculations of integral cross sections and rate constants for the title reaction. Calculations are carried out on the best available ground 1(2)A' global adiabatic potential energy surface of Deskevich et al. [J. Chem. Phys. 124, 224303 (2006)]. Converged state-to-state reaction cross sections have been calculated for collision energies up to 0.5 eV and different initial rotational and vibrational excitations, DCl(v = 0, j = 0 - 1; v = 1, j = 0). Also, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The narrow resonances can be assigned from the analysis of the wave function at the energy of the peak using a pseudo-spectral method[68, 82, 83], which in the case of using a modified Chebyshev propagator is implemented in Refs. [66, 84].…”
Section: Dynamical Methodsmentioning
confidence: 99%
“…The narrow resonances can be assigned from the analysis of the wave function at the energy of the peak using a pseudo-spectral method[68, 82, 83], which in the case of using a modified Chebyshev propagator is implemented in Refs. [66, 84].…”
Section: Dynamical Methodsmentioning
confidence: 99%
“…The correlation energies were scaled by a constant factor for all configurations to accurately reproduce the experimental reaction exothermicity. 20 On this PES, numerous theoretical and computational studies have since been performed using the QCT [23][24][25][26][27] or the QM [28][29][30][31][32][33][34][35] approach. It is found that, on the DHTSN PES, the QM calculated ro-vibrational state distributions of the product HF agree only qualitatively with the available experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated cross section for the formation reaction in the 0.01−1 eV energy interval was found to be in good agreement with the experimental values reported by Burley et al 31 More recent experiments reported rate constants for temperatures ranging from 20 to 200 K. The overall agreement was found to be good, but below 50 K, the measured values are larger than the simulated ones. 27,28 This was explained by a change of the behavior of the simulated cross section 28 as it will be further discussed below.…”
Section: Computational Methodologymentioning
confidence: 97%
“…In this work, we closely follow the previous study performed for the formation O + ( 4 S) + H 2 → OH + ( 3 Σ – ) + H­( 2 S) and exchange OH + ( 3 Σ – ) + H­( 2 S) → H­( 2 S) + OH + ( 3 Σ – ) reactions. In those studies, the ground quartet and doublet H 2 O + potential energy surfaces (PESs) were used (whose minimum energy paths (MEPs) are represented in Figure ). Their validity was assessed by comparing scattering results to available experimental data.…”
Section: Computational Methodologymentioning
confidence: 99%